Online News Framing of Ansar–Nyanyang during the 2024 Kepulauan Riau Gubernatorial Election - Bismar Arianto; Jamhur Poti; Reza Gemilang; Euis Ammelia; Intan Idiani (Yayasan Darussalam Bengkulu, 2026)
This study examines the digital political communication framing of Ansar Ahmad and Nyanyang Haris Pratamura in winning the 2024 Kepulauan Riau gubernatorial election. The main objective of this research is to identify the dominant framing patterns constructed through online news coverage and to explain how these frames contributed to the formation of the candidate pair’s electoral image. This study employed a qualitative descriptive-interpretive approach using secondary data obtained from online news articles published during the official campaign period. Data were collected through Google Advanced Search from verified national and local online media sources, using relevant keywords related to Ansar Ahmad, Nyanyang Haris Pratamura, and their campaign identity. After screening duplicate and irrelevant articles, the study analyzed 93 unique online news articles through thematic analysis and narrative analysis. The findings reveal that the Ansar–Nyanyang pair was framed through six dominant narratives: public support and legitimacy, credibility and competence, welfare and inclusive development orientation, commitment and readiness for implementation, identity, culture, and political values, and popularity and public mediation. These frames collectively constructed the pair as experienced, socially accepted, culturally connected, programmatically prepared, and electorally viable leaders. Local online media played a particularly significant role in amplifying these narratives, as most campaign-related coverage emerged from Kepulauan Riau-based outlets.